De novo CDKN1C variant in Beckwith–Wiedermann spectrum with atypical complications - Moriura, Yuri; Nishio, Yosuke; Ichimura, Shintaro; Noda, Haruka; Tanahashi, Yoshihiro; Yamamoto, Hikaru; Nakazawa, Yuka; Oso, Taichi; Sato, Yoshiaki; Takenouchi, Toshiki; Saitoh, Shinji; Muramatsu, Yukako; et al. (Human genome variation, 2025)
Beckwith–Wiedemann spectrum (BWSp) is a genomic imprinting disorder characterized by a wide range of clinical features. Here we report an infant with BWSp and atypical features, for whom long-read sequencing confirmed a de novo CDKN1C variant that occurred on the maternally inherited allele and excluded other genetic etiologies. These findings not only expand the BWSp concept but also highlight the potential value of allelic origin analysis in cases with atypical presentations.